THE TRAJECTORY OF CORINA DE VIVALDI IN THE BRAZILIAN PRESS BETWEEN 1874 AND 1880 - Silva, Helen de Oliveira [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2019)
Corina de Vivaldi (1859-1891) was a Brazilian writer who appeared in the press in the last years of 19th century. This paper describes and analyzes the author's production, devoid of studies, with particular attention to the written works when she was still very young, from 1874 until the year of 1880, period in which she was accompanied by her father, former Consul and trader Charles F. de Vivaldi (1824-1902). The analysis of texts may clarify what were Corina's opinions about the ongoing changes in the 1800s, whether they are in relation to education, to female empowerment and/or the role of the press. Thus, we seek to revisit the writer's action in the Brazilian newspapers between 1874 and 1880, which may have been neglected by the difficulty to identify her texts.
Keywords: the 19th century Brazilian press; Corina de Vivaldi